Spatial spread of Wolbachia in Rhagoletis cerasi populations - Bakovic, Vid; Schebeck, Martin; Telschow, Arndt; Stauffer, Christian; Schuler, Hannes (Biology letters, 2018)
The bacterial endosymbiont Wolbachia has been used to control insect pests owing to its ability to manipulate their life history and suppress infectious diseases. Therefore, knowledge on Wolbachia dynamics in natural populations is fundamental. The European cherry fruit fly, Rhagoletis cerasi, is infected with the Wolbachia strain wCer2, mainly present in southern and central European populations, and is currently spreading into wCer2-uninfected populations driven by high unidirectional cytoplasmic incompatibility. Here, we describe the distribution of wCer2 along two transition zones where the infection is spreading into wCer2-uninfected R. cerasi populations. Fine-scale sampling of 19 populations in the Czech Republic showed a smooth decrease of wCer2 frequency from south to north within a distance of less than 20 km. Sampling of 12 Hungarian populations, however, showed a sharp decline of wCer2 infection frequency within a few kilometres. We fitted a standard wave equation to our empirical data and estimated a Wolbachia wave speed of 1.9 km yr-1 in the Czech Republic and 1.0 km yr-1 in Hungary. Considering the univoltine life cycle and limited dispersal ability of R. cerasi, our study highlights a rapid Wolbachia spread in natural host populations.
Keywords: cytoplasmic incompatibility; Maďarsko; endosymbiont; European cherry fruit fly; Animals; Spatial Analysis; Wolbachia; Česká republika; prostorová analýza; modelling; zvířata; Hungary; Tephritidae; Czech Republic